PENGGUNAAN VARIASI FILTER PADA WINDOWING LUNG PADA PEMERIKSAAN CT SCAN THORAX - Sudiyono Sudiyono; Rini Indrati; Muhammad Riefki Jadmika (Jurnal Imejing Diagnostik (JImeD), 2020)
Background: Filter is an image processing parameter applied to raw data used to determine the attenuation value of each pixel of CT Scan imaging, and it serves to minimize the occurrence of star patterned streak artifacts formed on the CT images. The use of typical Y-sharp or Smooth filters is common for the thoracic CT imaging in the clinic. Yet, the studies to compare which of the typical filters that provide a good imaging technique were clinically limited to find in practices. The purpose of this study is to know wheter there is a difference or not in the anatomical image resolved amongst the thoracic CT images when using the Y-Sharp and Smooth filters; and to determine which of the filter that produces the better image quality by comparison.Methods: This is quantitative research with approached the pre-experimental design with the static-groups of comparison. Image data were taken from the raw data of the 10 patients who underwent CT Scan Thorax examinations. All the image data were reconstructed by means of using the Y-Sharp and Smooth filters. Assessment of the images were performed by 2 radiologists. The Cohen's Kappa was used for image evaluators agreement where the Wilcoxon Test was applied to test the hypotheses.Result: The result of this study showed that there is a significant difference in anatomical organ visualization of the thoracic CT images between filter the Y-Sharp and Smooth filters with p-value 0.005. The use of Y-Sharp filter is better as it produces a high spatial image resolution.Conclusion: The anatomical organs of the thoracic CT images are visually reproduced when the Y-sharp filter is employed. The comparison between the two different filter uses deems significance.